Pseudoautosomal repeat displays higher variability in Blacks than in Caucasians - Rappold, Gudrun; Henke, Anja; Pohlschmid, Marita; Huisman, Titus H. J. (Human genetics, 1992)
DNA patterns from a pseudoautosomal variable number tandem repeat-like minisatellite (locus DXYS20) were compared in two samples: a Caucasian and a Black sample. We defined 3 types of DNA patterns named A, B and C, and found that these patterns have different frequencies in the Caucasian and Black groups. A set of alleles (the C group) in 48% of the Black sample is not found in the Caucasian sample. We also found a greater degree of fragment-size variability among Black individuals than among those of Caucasian origin. The large degree of ethnic variation indicates that this locus will be useful in population genetic studies.